Hubungan Spasial Parameter Geologi Bawah Permukaan dan Kualitas Air Tanah untuk Memahami Intrusi Air Laut di Cekungan Semarang: Spatial Integration of Subsurface Geological Parameters and Groundwater Quality to Understand Seawater Intrusion in the Semarang Basin - Marsya Nindia Nindia; Athira Farah Fathania Hanum; Lies Tsiqoyati Rohmah (Jurnal Teknik Sumber Daya Air, 2026)
Seawater intrusion is one of the most significant forms of groundwater quality degradation in coastal areas, particularly in rapidly urbanizing cities such as Semarang. The increasing demand for clean water driven by population growth and industrial activities in coastal zones has resulted in excessive pressure on aquifers, ultimately allowing seawater to infiltrate the groundwater system. The Semarang Basin, as a zone of high-porosity sediment accumulation, is especially vulnerable to this phenomenon due to its lithological characteristics and the presence of active geological structures. This study aims to understand the spatial relationship between subsurface geological parameters and groundwater quality in the context of seawater intrusion. A descriptive and spatial approach was employed using secondary data, including geological maps, gravity anomalies, salinity maps from 2016 and 2022, and historical chloride concentration trends from 1992 to 2011. Analysis was conducted using ArcGIS software to identify correlations between fault structures, lithology types, and the distribution of saline water zones. The results indicate that seawater intrusion has developed along the direction of active fault structures and permeable lithologies within the basin, with an expansion of high-salinity zones (>1000 mg/L) from northern to central Semarang over a six-year period. Historical trends in rising chloride levels further support the indication that the intrusion process is occurring progressively. These findings highlight the urgent need for continuous groundwater quality monitoring and the protection of aquifer recharge zones as key mitigation strategies against the spread of seawater intrusion in densely populated coastal areas.